ROP-like retinopathy in full/near-term newborns: A etiology, risk factors, clinical and genetic characteristics, prognosis and management - Sun, Limei; Yan, Wenjia; Huang, Li; Li, Songshan; Liu, Jia; Lu, Yamei; Su, Manxiang; Li, Zhan; Ding, Xiaoyan (Frontiers in Medicine, 2022)
Purpose: ROP-like retinopathies (ROPLR) could occur in full/near-term newborns. The causes and clinical features are still largely elusive. This study focused on the risk factors, clinical and genetic characteristics, treatment and outcome, and prognosis of ROPLR. Methods: A total of 47 consecutive full/near-term newborns during 2016–2017 with ROPLR were included. The clinical and genetic characteristics, treatment and outcome, prognosis, and potential underlying aetiology of ROPLR were were analyzed. Results: Ninety-one eyes of 47 infants were found to have ROPLR. The ROPLR regressed completely in 65.9% and partially in 20.9% of eyes without any interventions. FEVR-positive fundus findings were allocated in 12 neonates (group A), perinatal hypoxia-ischemia were categorized in 17 neonates (group B), and the other 18 neonates were categorized in group C. Compared to those in group B/C, infants in group A had significantly more severe retinopathy (stage 4/5, P＜0.001) and more treatments (p < 0.001). Conclusions：Perinatal hypoxia-ischemia might be a major risk factor for ROPLR, in which spontaneous regression was common. FEVR, confirmed by positive family findings and genetic testing, might be the second risk factor of ROPLR, in which retinopathy is more severe and treatment is needed.